Regular Physical Activities Inhibit Risk Factors of the Common Cold Among Chinese Adults - Tu, Renjie; Lu, Yifan; Tao, Kuan (Frontiers in Psychology, 2022)
Background Physical activity (PA) has a significant health impact worldwide and has been linked to a lower risk of the common cold. Objective The aim of this study was to estimate the form of PA among Chinese adults and the correlation between PA and number of the common cold in China's eastern, central, and western areas. Design A cross-sectional study. Setting China's eastern, central, and western regions from 30 November 2020 to 30 March 2021. Patients A total of 1,920 healthy participants, who aged over 18 years old, with Internet access, were enrolled, and then self-reported PA behaviors and number of the common cold were collected. Measurements The authors calculated preference, intensity, frequency, and duration of PA in Chinese based on gender, age, and broad occupational categories and explored the potential effect between these factors and the common cold. Results Approximately 20.4% of participants reported not participating in sports regularly. Except for gender, there were significant differences in PA preference and intensity among the remaining individuals (P <0.05). Sixteen common exercises were divided into three intensity levels by the Borg CR10 Scale: low- (5), moderate- (8), and high-intensity exercises (3), and the corresponding intensity, frequency, and duration were computed with significant differences (P <0.05). The most popular workouts are “Brisk walking” and “Running.” Age, sex, and occupation had no significant effect on colds (P > 0.05). However, intensity shows a U-shaped dose-response relationship with colds, whereas the frequency and duration have an inverse dose-response relationship (P <0.05). High intensity combined with high frequency increased colds the most. Nevertheless, non-exercise groups always have the most colds in each comparison. Limitations The result may be vulnerable to recall bias. Conclusion Intensity showed that U-shape, frequency, and duration showed inverse response to the number of colds last year, but age, sex, and occupation had no significant effects. High intensity and high frequency mixed increased colds the most, regardless of duration.